Gold nanoparticle modified electrodes show a reduced interference by Cu(II) in the detection of As(III) using anodic stripping voltammetry - Dai, X; Compton, R (2005)
Interference by Cu(II) causes serious problems in the detection of As(III) using anodic stripping voltammetry at gold electrodes. The behavior of Cu(II) and As(III) were examined at both a gold macro electrode and two kinds of gold nanoparticle modified electrodes, one where gold particles are deposited on glassy carbon (GC) and the other where basal plane pyrolytic graphite (BPPG) is the substrate. The sensitivity of As(III) detection was higher on gold nanoparticle modified electrodes than those on a macro gold electrode by up to an order of magnitude. In addition, the stripping peak of As(III) was narrower and more symmetric on a gold nanoparticle-modified GC electrode, leading to analytical data with a lower limit of detection. At a macro gold electrode, the peak currents of Cu(II) were higher than those on gold nanoparticle modified electrodes. Accordingly, through the use of gold nanoparticle modified electrodes, the effect of copper interference to the arsenic detection can be reduced. © 2005 Wiley-VCH Verlag GmbH and Co. KGaA.